Analysis of Language Errors in the Field of Phonology Kick Andy Double Check Event - Tasya, Afratul; Annisa Putry, Chairany (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Language is sounds that are bound by certain characteristics, pronounced through human speech organs, and used to communicate. The use of language in the communication process, both spoken and written, has rules that must be observed. However, in practice in everyday life, there are still many errors in the language process. One form of language error that is often found is errors in phonology or language problems related to the pronunciation of word sounds. Through this research, forms of language errors in the field of phonology will be presented in the interview with the National Police Chief Listyo Sigit Prabowo. This research was conducted using a qualitative descriptive method using note-taking techniques. Sources of data were obtained based on direct utterances during the interview process by the Indonesian National Police Chief Listyo Sigit Prabowo in the television show Kick Andy Double Check episode "Cut Head Ala Kapolri" which aired on September 18 2022. This study focused on phonological errors in the form of changes and omissions of phonemes that occurs in every pronunciation of the word. Based on the results of the study, many language errors were found due to changes and omissions of phonemes, both vowel and consonant phonemes.